Asymptotic Behavior of Boson Regge Trajectories - Trushevsky, A.A. (Ukrainian Journal of Physics, 2021)
The asymptotic behavior of boson Regge trajectories is studied. Upper and lower bounds on the asymptotic growth of the trajectories are obtained using the phase representation for the trajectories and a number of physical requirements. It is shown that, within the assumptions made, the asymptotic behavior of the trajectories is a square root.